Новые виды рода Urophora (Diptera, Tephritidae) из Узбекистана - Корнеев, В.А. (Вестник зоологии, 1985)
Urophora volkovae sp. n.- similar to U. christophi and U. egestata Hering; from all species without wing crossband differs in an indistinct area covered with dark microtrichia in apical third of the wing; type locality: Uzbek SSR, Chatkalskiy Reserve, Bashkyzylsai). U. beikoi sp. n.- similar to U. pia Hering, differs in wide yellow pleural stripe; type locality: Uzbek SSR, Chatkalskiy Reserve.